From Startups to Unicorns : The Rise of Digital Entrepreneurship in India - Dr. Ashok P. Jadhav; Dr. Tejpal J. Moharekar (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Digital entrepreneurship in India has emerged as a key driver of innovation and economic growth, bolstered by rapid technological advancements and supportive government initiatives. However, entrepreneurs face significant challenges, including infrastructural deficits, skill gaps, and regulatory hurdles. This paper examines the evolution of digital entrepreneurship, current state of digital entrepreneurship in India, identifies key challenges, and explores future prospects to create an inclusive and sustainable entrepreneurial ecosystem. The analysis is supported by statistical insights and references to existing research, emphasizing the role of government initiatives, technology adoption, and the entrepreneurial ecosystem.